Estimating the cost of young stock mortality in livestock systems—An application to sheep farming in Ethiopia - Otte, Joachim; Schnier, Christian; Allan, Fiona K.; Salmon, Gareth; Wong, Johanna T.; Minjauw, Bruno (Frontiers in Veterinary Science, 2024)
Introduction In sub-Saharan Africa, pre-weaning young stock mortality (YSM) is in the order of 20 to 30% across most livestock species and production systems. High YSM has significant economic implications for livestock keepers, but few studies provide estimates of the “cost of YSM.” This study explores a bio-economic herd modeling approach to estimate the “cost of YSM” at farming/livestock system level. Methods The static zero-growth version of DYNMOD was used to calculate the annual physical and monetary output of a sheep flock consisting of 100 breeding females at different levels of lamb mortality. Production parameter values and prices were taken from recently published research. Calculations were carried out for values of lamb mortality decreasing from 30% to 0% in 5% intervals, with 20% representing the “baseline” YSM. Calculations were repeated for a “high” fertility scenario (100% vs. 59% parturition rate) to gauge the sensitivity of the cost of YSM to another parameter determining flock productivity. Results The relation of revenue per head and YSM is close to linear over the range of analyzed YSM with 1% decrease in YSM resulting in an increase in revenue per animal of approximately 1%. At the higher fertility rate, the absolute cost of YSM to sheep farmers is higher while the relative increase in revenue per animal resulting from YSM reduction is lower. The estimated difference in revenue of the 100-ewe flock between the 20% and 0% lamb mortality scenarios (at baseline fertility) amounts to approximately USD 90 per additionally surviving lamb, which is far above its market value. Discussion Reduced lamb mortality ultimately impacts flock revenue through increased sales of “mature” animals, which embody the value of a lamb plus the revenue/profit from raising it to marketable age/weight. The modeling results suggest that foregone profit is an important component of the systemic “cost of YSM.” Consequently, expected profit per animal, in addition to its current market value, is essential for estimating the absolute cost of YSM at farming system level.